EFEKTIFITAS PENYULUHAN MENGGUNAKAN MEDIA POSTER TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI PUSKESMAS BANDUL - Rizki Natia Wiji; Heriyeni, Heni (Universitas Batam, 2025)
The coverage of complication detection in pregnant women, especially at the Bandul Health Center, has increased in the last three years, where in 2022 it was 2.5%, in 2023 it was 3.5%, and in 2024 it increased again to 3.8% of the 20% target of pregnant women. This can be anticipated by increasing the knowledge and attitudes of pregnant women about pregnancy danger signs. One of the media that can be used posters. his study aimed to determine the effectiveness of counseling using poster media on the knowledge and attitudes of pregnant women about pregnancy danger signs. The research design was Pre-experimental with a one group pre-test and post-test design. The population in the study were all pregnant women registered in the Bandul Health Center working area in January - June 2025 as many as 90 people. The sample included 27 pregnant women selected through purposive sampling. The instruments used were questionnaires and post-test media. There is Effectiveness of Counseling Using Poster Media on the Knowledge and Attitudes of Pregnant Women Regarding Danger Signs of Pregnancy at the Bandul Community Health Center p-value = 0.000. The output of the study is a poster. at the Bandul Community Health Center. It is hoped that this study can improve the knowledge and attitudes of the community, especially pregnant women, about danger signs of pregnancy and it is hoped that respondents will actively seek information and regularly check their pregnancy with health workers.